EKONOMI SUFISTIK (SPIRITUALITAS DALAM BERMUAMALAH) - Maghfur, Ifdlolul (MALIA (TERAKREDITASI), 2017)
Sufism is a science that studies the divine and related aspects of Gods character. The essence of tauhid in Islam itself is a self-surrender of Gods will, both of worship and of muamalah.The purpose of production is to meet individual needs and realize the independence of the ummah. The purpose of production in the individual level is the fulfillment of the individuals needs perfectly based on the feasibility of the times and the environment. The purpose of production in the level of ummah is the fulfillment of the ability, expertise and infrastructure with which human beings can carry out their religious affairs affairs.Therefore Islam requires its people to work to meet the needs of life, the benefit of the family, the benefits of society and to prosper the earth.Muslims, should not only be diligent in worship, but must also be true in your practice. In other words, the Muslims besides having ritual piety, must also have social piety. Muslims must be able to implement their noble values to Allah SWT in their daily activities, both in political, social and economic activities. Values of tauhid should be implemented in our daily lives eg in economic activities such as honesty, fairness, trust, and transparency.